Metodologia da problematização no processo ensino-aprendizagem de educação em saúde na percepção de estudantes de enfermagem - SANTOS, Joyce Petrina Moura (2020)
The purpose of this study is to understand the perception of undergraduate nursing students about the teaching-learning process through the methodology of Problematization in the teaching of health education. The study is descriptive, with a qualitative approach, developed in a public university of the Northern region of Brazil. The subject searched for is part of the second year of the nursing course and focuses on the Health Education Processes. The participants were 15 undergraduate students who were regularly enrolled in the fourth semester of nursing in the first semester of 2019. The group chosen for the research, the students should be properly enrolled, have studied in the last 6 months, have attendance in classes ≥ 75%, participate in 100% of the practical activities of the discipline where the method of the problem was used . Data collection was performed through a semi-structured interview. For the analysis of the data, the open and axial coding phases of the constant comparisons method (STRAUSS; CORBIN, 2008) ordered in the trial version of the Atlas TI® program were used. At the end of the open coding were generated 21 codes and during the axial coding 6 categories were generated, being: "Preferences related to learning styles and teaching methods"; "Active Methodology"; "Methodology of the Problematization with the Arch of Maguerez"; "Health Education Planning: Understanding the students"; "Obstacles and Challenges experienced by students"; "Evaluations and propositions for better development of the teaching-learning process". With the study, it was possible to verify that the Problem Array presents a strong potential for teaching health education planning, since it has characteristics of participatory planning and that corroborate to a liberating education in search of meaningful learning. In this sense, the teaching process through the methodology of the problematization was effective, since the academics report that they learned to do educational planning through the Arch of Maguerez. In addition, they also had students who used Arco as a direct planning tool, directly reporting the steps of the method as a participatory educational planning mechanism.